Envy influences interpersonal dynamics and team performance: Roles of gender congruence and collective team identification - TAI, Kenneth (Institutional Knowledge at Singapore Management University, 2024)
Our research extends past envy research by considering how envy and gender congruence shape interpersonal dynamics at the dyadic level and their bottom-up effects for team performance. Integrating social comparison theory and social identity theory, we examine when and how dyadic level envy influences team performance. Using time-lagged data from 428 dyads of 161 employees in 51 teams, our results show that envious employees are likely to engage in interpersonal deviance directed toward envied team members and that envied employees are likely to seek advice from envious team members. Gender congruence further influences these relationships, with different patterns for males and females. Specifically, while envious male employees are more likely to engage in interpersonal deviance toward envied male team members (i.e., male–male dyads), envied female team members are more likely to ask envious female employees for advice (i.e., female–female dyads). Interpersonal dynamics involving envy have performance implications, such that team performance is worse where envious employees are more likely to engage in interpersonal deviance directed toward envied team members, in comparison to teamswhere this relationship is weaker. Finally, collective team identification mitigates the negativeeffect of envious employees’ interpersonal deviance on team performance.